METABOLIC ACIDOSIS VS TRANSAMINASES LEVEL IN DIAGNOSIS AND PREDICTING PROGNOSIS OF ACETAMINOPHEN POISONING - RAGIA M. HEGAZY; WALEED H. ALMALKI; HALA F. M. KAMEL; SAMEER H. FATANI (International Journal of Pharma and Bio Sciences, 2012)
Background: Paracetamol (APAP) is the most famous drug used in the world to relieve of pain and used as an antipyretic. Paracetamol overdose induces liver damage and is a well known hepatotoxic drug. This study was aimed to determine the incidence of acidosis in acetaminophen overdose with the time of N- Acetyl Cystiene (NAC) administration and correlation of late acidosis and death in acetaminophen overdose. Materials and methods: The data were obtained from the patients’ files admitted to AL-Noor Hospital due to the ingestion of Paracetamol overdose. The Data on Paracetamol levels, liver transaminases (AST, and ALT), arterial blood gases, lactate levels and serum electrolyte levels had been collected from files. Results: Fifty five cases were divided into three groups: Group I (33 cases) had early acidosis with toxic APAP dose; Group II (9 cases) had late acidosis with toxic APAP dose; and Group III (13 cases) with non toxic APAP ingestion or developed acidosis. In 65.45% of cases, the age was between 14-30 years. Most of the cases were females (74.5%), and the adult was 78.77% while 21.23% were children. There was a positive significant relation (P < 0 .05) Between APAP toxic doses, early NAC administration, early anion gap acidosis and complete recovery. Also, there was a positive significant relation (P < 0.05) between, APAP toxic doses, late NAC administration, late lactic acidosis with coma and death. There was no significant relation (P > 0.05) between serum transaminases and toxic APAP level or prognosis. Conclusion: Metabolic acidosis are a specific indicator for APAP heptotoxicity than serum transaminases